Semicontinuous Microemulsion Polymerization of Polymeric Nanoparticles of Poly(cyanoacrylates) and Poly(caprolactone) - Gerardo León-Sánchez; Eulogio Orozco-Guareño; Oscar Guillermo Zúñiga-González; Luisa Fernanda Briones-Márquez; Raúl R. Quiñonez-López; Jesús Baudelio Campos-García; María de Jesús Palacios-Sánchez (Molecules, 2025)
Polymeric nanoparticles based on poly(ethyl cyanoacrylate) (PECA) and poly(ε-caprolactone) (PCL) were synthesized via semicontinuous microemulsion polymerization for potential biomedical applications. A systematic evaluation of four surfactants (Tween 80, Alkonat L70, Genapol LRO, and Brij-20) was carried out to determine their effects on micelle formation and particle size. Brij-20 enabled the formation of nanoparticles under 100 nm, with optimal conditions identified at 4% surfactant concentration and pH 1.75. The polymerization process included acid-catalyzed ring-opening of ε-caprolactone, followed by the semicontinuous addition of ethyl-2-cyanoacrylate under an inert atmosphere. Copolymerization was confirmed through FT-IR spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, and differential scanning calorimetry, revealing a glass transition temperature (Tg) of 110.9 °C, indicating PECA as the dominant phase. Thermogravimetric analysis showed two decomposition events corresponding to each polymer. Transmission electron microscope analysis revealed nanoparticles averaging 51.74 nm in diameter. These findings demonstrate the feasibility of producing PECA-PCL nanoparticles with controlled size and composition, suitable for drug delivery and other biomedical uses.